Kesalahan Siswa Dalam Mengerjakan Soal Cerita Sistem Persamaan Linear Berdasarkan Kriteria Watson - Vikra Vikra; Philoteus E. A. Tuerah; Victor R. Sulangi (Simpati, 2024)
This study tries to identify the faults and circumstances that lead students to miscalculate when attempting to solve word problems involving a system of linear equations with two variables using Watson's criteria. This kind of study employs qualitative, descriptive research methods. Data was gathered using a variety of methods, including analysis, interviews, documentation, and a written test with five-item description questions. Class VIII students from SMP Negeri 5 Tondano 2022/2023 served as the study's sources and subjects. They were chosen after careful consideration. Data analysis techniques in this study through data reduction, data presentation, and conclusions. The results showed that the students' errors were incorrect data, inappropriate procedures, response level conflicts, and skills hierarchy problems. The causative factors are that students are not careful when writing answers, students think that conclusions do not need to be written down, students forget how to change the story form questions into the form of mathematical models or the principles used are still wrong, students forget to write examples, students are wrong in operating numbers either subtraction, addition, division and multiplication, students forgot to write conclusions, students were unable to write down existing data, students did not know how to answer questions, students forgot to find x and y values using the substitution method, students used wrong marks in mathematics, students ran out of time when solving problems.